Evaluating a school–industry partnership using the CIPP Model: Evidence from the light vehicle engineering program at SMK Ma’arif Salam - Ilham Cahyadi; Wardan Suyanto; Wan Ameran bin Wan Mat (Jurnal Pendidikan Vokasi, 2025)
Partnerships between vocational schools and industry are expected to strengthen the link between learning and workplace demands; however, the extent to which partnership programs are implemented effectively is not always systematically evaluated. This study evaluates the partnership program between SMK Ma’arif Salam and PT Astra Daihatsu Motor (ADM) in the Light Vehicle Engineering Department using the CIPP (Context, Input, Process, Product) evaluation model. Respondents consisted of the Principal, Vice Principal for Public Relations, Head of Department, teachers, and industry partners. Data were collected through validated questionnaires, interviews, and document analysis, and were analyzed using descriptive statistics and qualitative thematic analysis. The overall achievement level of the partnership program reached 84% (good), with context 89% (very good), input 84% (good), process 84% (good), and product 65% (fair). The results indicate that although the program is generally well managed, several persistent challenges remain: high teacher workload, limited coordination with industry, inadequate facilities and funding, limited industrial experience among teachers, uneven implementation of SOPs, low student motivation, and suboptimal graduate absorption. The product component shows the lowest performance, suggesting that the program’s outcomes have not fully translated into improved student competence and employability. This evaluation provides evidence-based guidance for prioritizing improvement efforts, particularly in strengthening teacher development, aligning facilities with industry standards, expanding internship opportunities, and enhancing curriculum implementation. The findings also offer transferable insights for other vocational schools and industries implementing similar partnership schemes.